2013
DOI: 10.1016/s1995-7645(13)60092-9
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective and antioxidant capacity of Melochia corchorifolia extracts

Abstract: From the results obtained during the study it could be concluded that M. corchorifolia aerial part extracts have antioxidant and hepatoprotective components. Further study is necessary for isolation and characterization of bioactive molecules which are responsible for hepatoprotective and antioxidant activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 29 publications
0
43
0
Order By: Relevance
“…The search of biologically active compounds from medicinal plants has always been of great interest to scientists looking for new sources of useful drugs against different hazardous diseases. Many plant species have been investigated in the search for antioxidants but generally there is still a demand to find more information concerning the antioxidant potential of plant species [18,21,35,36]. Many studies have shown that natural antioxidants in medicinal plants closely related to their biofunctionalities, such as the prevention or suppression of aging and many diseases associated with oxidative stress, cancer, cardiovascular diseases, rheumatoid arthritis, autoimmune diseases and AIDS [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The search of biologically active compounds from medicinal plants has always been of great interest to scientists looking for new sources of useful drugs against different hazardous diseases. Many plant species have been investigated in the search for antioxidants but generally there is still a demand to find more information concerning the antioxidant potential of plant species [18,21,35,36]. Many studies have shown that natural antioxidants in medicinal plants closely related to their biofunctionalities, such as the prevention or suppression of aging and many diseases associated with oxidative stress, cancer, cardiovascular diseases, rheumatoid arthritis, autoimmune diseases and AIDS [37].…”
Section: Discussionmentioning
confidence: 99%
“…The results were showed in mean ± SEM. The Percentage Inhibition and 50% Inhibition Concentration's (IC50) were calculated [18,21]. The each values were studied against blank in every assay of scavenging activity.…”
Section: In Vitro Antioxidant Activitymentioning
confidence: 99%
“…If anti-oxidants present in the test compound, a blue to yellow color change occurred due to reaction with DPPH (Rao et al, 2013).…”
Section: In Vitro Free Radical Scavenging Activitymentioning
confidence: 99%
“…Superoxide scavenging activity of the selected extract and its fractions were evaluated as per standard method-induction of superoxide free radical generation by riboflavin, the corresponding reduction by nitroblue tetrazolium and the absorption of light at 560 nm (Rao et al, 2013).…”
Section: In Vitro Free Radical Scavenging Activitymentioning
confidence: 99%
“…Further examination is necessary for isolation and characterization of bioactive molecules which are responsible for hepatic protective and antioxidant activity, what may open a new research topic in our future trials [9].…”
Section: Noni-juicementioning
confidence: 99%